TOTAL QUALITY MANAGEMENT OF LIBYAN SCHOOLS IN MALAYSIA - m alfegeh, Zenib Mohamed; Karim, Abdul Malik Amrullah (Proceeding of International Conference on Islamic Education (ICIED); Vol 2 No 1 (2017): Proceeding of International Conference on Islamic Education (ICIED), 2017)
The term of TQM in education refers to continuous development of management strategy produced by the educational institution adopted on a set ofprinciples in order to bring out its main entrance, which is the student on highest quality in all aspects growing ofthe mental, psychological, social, moral and physical in order to satisfy the student to become required after his graduate in the labor market and to satisfy all the organs ofthe society benefiting ofthis alumnus. The aim of this research is to highlight on the concept of TQM and to know the importance of the needs of TQM in education and to know the TQM standards in education and also, to know the objectives ofapplying TQM in educational institutions, as well as, to understand the reality ofapplying TQM in Libyan educational institutions, to reach some results and recommendations that will contribute to achieve the desired educational quality. In this research we conclude that necessity adopt the concepts of TQM and apply it in our educational system if we really want to grow by education and achieve the desired educational quality. As well as, we should supply our educational institutions by highly educated managers with the necessary administrative and educational skills to manage it well. And also by lecturers qualified scientifically and educationally to do their duty to the fullest to the students and society and must create and provide the appropriate environment and help to good education and effective within educational institutions. It has been shown us through the results that the managers believe the Libyan educational institutions in Malaysia applying the total quality management that both of school management and lecturers are characterized by quality and abide by the principles of total quality management and its standards.